The use of measurement frameworks to explore the qualities of test items - Deborah Oluwafunmilola Tobih; Musa Adekunle Ayanwale; Olufemi Abiodun Ajayi; Modupe Victoria Bolaji (Institute of Advanced Engineering and Science, 2023)
Psychometricians and researchers have grown increasingly concern about students’ performance. It is noteworthy from observation in the selected university of education in Nigeria that many of these students do not attend lectures for general courses particularly EDU 222 (tests and measurement) due to overcrowded lecture halls, the classroom climate factor, and other latent factors, such as exam conditions, test anxiety among others. Consequently therefore, students’ performance in EDU 222 does not significantly correlate with these challenges. The characteristics of the item parameter of the Tests and Measurement achievement test at the selected University of Education in Ogun State, Nigeria, were therefore examined in this study using measurement theories. The study employed an ex-post facto research of non-experimental design. Purposive sampling was used to select 6,203 second-year undergraduates offering EDU 222 for the 2018/2019 academic year. To analysis students’ responses to 30 multiple-choice questions on tests and measurement, factor analysis, item calibration, an independent sample t-test with a significance threshold of 0.05 were utilized with empirical reliability of 0.64. The results showed the test items satisfied the three-parameter logistics model and uni-dimensionality assumption. The findings also showed that the item response theory (IRT) eliminated 7 items due to guessing, while the classical test theory (CTT) eliminated 13 items. The test is prone to guessing, thus, helps pupils do better on the exam. To establish parameter estimates during test development, higher education institutions (HEIs) should employ the use of IRT.